Epidemiological, anatomopathological, and immunophenotypical aspects of cutaneous lymphomas in dogs - Mazaro, Renata D.; Lorenzetti, Douglas M.; Leite, Suzana M.G.; Masuda, Eduardo K.; Da Costa, Leonardo D.; Vasconcelos, Rosemeri O. [UNESP]; Dantas, Antonio Flávio M.; Lacerda, Luciana C.; Da Silva, Tereza Cristina; Motta, Marco Aurélio A.; Cogliati, Bruno; Fighera, Rafael A. (My University, 2023)
Cutaneous lymphomas are uncommon tumors in dogs that can occur as epitheliotropic and non-epitheliotropic types. The epitheliotropic type comprises three, already well established, distinct clinicopathological presentations. However, the non-epitheliotropic lymphoma, despite its poor characterization, represents a heterogeneous group of not yet correlated presentations that can mimic different skin tumors, configuring a diagnostic challenge. Therefore, this study’s main aim was to establish whether there is a correlation between the macroscopic presentation and the histological subtypes of cutaneous non-epitheliotropic lymphoma in the population of dogs involved in this study. Additionally, we aimed to determine the prevalence of each type and histological subtype of canine cutaneous lymphoma and describe the epidemiological and anatomopathological characteristics of the presented cases. From a total of 38 cases of cutaneous lymphoma diagnosed in dogs, 17 (44.7%) were considered as epitheliotropic and 21 (55.3%) as non-epitheliotropic. From the 17 cases of cutaneous epitheliotropic lymphoma, 13 (34.2%) and four (10.5%) were subclassified as mycosis fungoides and pagetoid reticulosis, respectively. The cases of cutaneous non-epitheliotropic lymphoma included were: anaplastic large T-cell lymphoma (ALTCL – 9/21, 23.9%), peripheral T-cell lymphoma, unspecified (PTCL-NOS – 4/21, 10.5%), subcutaneous panniculitis-like T-cell lymphoma (SPTCL – 4/21, 10.5%), diffuse large B-cell lymphoma – immunoblastic type (DLBCL – 2/21, 5.2%), lymphomatoid granulomatosis (LYG – 1/21, 2.6%), and marginal zone lymphoma (MZL) of mucosa-associated lymphoid tissue (MALT) - lymphoplasmacytic variant (1/21, 2.6%). Based on the anatomopathological findings, it was possible to infer that when faced with multiple, nodular or placoid skin lesions, predominantly on the trunk and limbs, the diagnosis is more likely to be consistent with ALTCL. Whereas, with solitary skin nodules or plaques, PTCL-NOS will be the most frequently observed histological type. When these lesions are exclusively located in the subcutaneous tissue, one should first think about SPTCL and, more rarely, DLBCL. Regarding to epitheliotropic cutaneous lymphomas, the most commonly observed type in dogs is the cutaneous form of mycosis fungoides, especially in the pre-mycotic and mycotic phases. We hope that this information can assist veterinary clinicians and pathologists in their diagnostic routines and contribute to the characterization of non-epitheliotropic cutaneous lymphomas in the canine species.
Keywords: cutaneous tumors; dermatopathology; dogs; Skin lymphomas; uncommon lymphomas